2022
DOI: 10.21037/atm-22-2135
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic network changes associated with cognitive impairment in patients with hearing loss and tinnitus: a resting-state functional magnetic resonance imaging study

Abstract: Background: Hearing loss and tinnitus often occur concurrently and play a vital role in the development and progression of cognitive impairment (CI). However, the exact mechanism remains unclear. This study aimed to investigate the changes in intrinsic brain connectivity in patients with hearing loss and tinnitus accompanied by CI.Methods: A total of 24 hearing loss and tinnitus patients with CI, 23 hearing loss and tinnitus patients with cognitive normality (CN), and 20 healthy controls (HCs) underwent restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Several auditory brain areas were selected as features in our study (Supplementary Figure S1), including the thalamus, temporal pole: superior temporal gyrus, temporal pole: middle temporal gyrus, inferior temporal gyrus, middle temporal gyrus, and superior temporal gyrus, which is consistent with reported studies (Xu et al, 2019a;Persic et al, 2020;Yang et al, 2021). Along with these auditory regions, frontal, parietal and hippocampal features selected in our study overlapped with areas in patients with hearing loss and cognitive impairments (Banaszkiewicz et al, 2021;Ponticorvo et al, 2021;Shen et al, 2021;Ma et al, 2022). Recent research has demonstrated occipital involvement in patients with auditory deprivation, suggestive of cross-modal reorganization (Campbell and Sharma, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…Several auditory brain areas were selected as features in our study (Supplementary Figure S1), including the thalamus, temporal pole: superior temporal gyrus, temporal pole: middle temporal gyrus, inferior temporal gyrus, middle temporal gyrus, and superior temporal gyrus, which is consistent with reported studies (Xu et al, 2019a;Persic et al, 2020;Yang et al, 2021). Along with these auditory regions, frontal, parietal and hippocampal features selected in our study overlapped with areas in patients with hearing loss and cognitive impairments (Banaszkiewicz et al, 2021;Ponticorvo et al, 2021;Shen et al, 2021;Ma et al, 2022). Recent research has demonstrated occipital involvement in patients with auditory deprivation, suggestive of cross-modal reorganization (Campbell and Sharma, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…Several auditory brain areas were selected as features in our study ( Supplementary Figure S1 ), including the thalamus, temporal pole: superior temporal gyrus, temporal pole: middle temporal gyrus, inferior temporal gyrus, middle temporal gyrus, and superior temporal gyrus, which is consistent with reported studies ( Xu et al, 2019a ; Persic et al, 2020 ; Yang et al, 2021 ). Along with these auditory regions, frontal, parietal and hippocampal features selected in our study overlapped with areas in patients with hearing loss and cognitive impairments ( Banaszkiewicz et al, 2021 ; Ponticorvo et al, 2021 ; Shen et al, 2021 ; Ma et al, 2022 ). Recent research has demonstrated occipital involvement in patients with auditory deprivation, suggestive of cross-modal reorganization ( Campbell and Sharma, 2020 ).…”
Section: Discussionmentioning
confidence: 83%